A EVALUASI PROGRAM INDONESIA PINTAR DALAM UPAYA PEMERATAAN PENDIDIKAN - jumanah; Hilda Rosita (Epistemik Press, 2023)
This study aims to analyze the effect of the smart Indonesia program in an effort to equalize education in Indonesia. The data used in this study were obtained through a literature study by searching, collecting and reading various journals or articles about the Smart Indonesia program that has an impact on equal distribution of education in Indonesia. In the implementation of the Smart Indonesia Program itself, there are still various obstacles which are one of the inhibiting factors in suppressing the decline in the dropout rate in Indonesia. For example, the inaccurate determination of prospective students receiving the Smart Indonesia Program, delays in disbursing funds, insufficient socialization of this program, the length of the process in verifying card ownership, and the level of awareness of the guardians of students regarding the allocation of Smart Indonesia Program assistance is still lacking. That way the government's efforts to reduce the dropout rate are less than optimal which has an impact on equal distribution of education in Indonesia. So that the implementation of the smart Indonesia program needs to be supported by several factors that encourage this program to run more effectively.